2009
DOI: 10.1093/jac/dkn523
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel macrolide efflux gene, mef(B), found linked to sul3 in porcine Escherichia coli

Abstract: A new macrolide efflux protein, Mef(B), with 38% amino acid identity to Mef(A), has been characterized and represents the second member of the mef family of genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 11 publications
0
36
1
Order By: Relevance
“…Among these, the AcrAB-TolC like RND-type efflux pumps present in different members of the genus are probably the best characterized efflux pumps of Enterobacteriaceae. The effect of AcrAB-TolC on the extrusion of different macrolides has been shown by developing defective (Liu et al, 2009) Ery: erythromycin; Azm: azithromycin; Tel: telithromycin; Jos: josamycin; Clar: clarithomycin; ? : proposed association.…”
Section: Chromosomal Efflux Pumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the AcrAB-TolC like RND-type efflux pumps present in different members of the genus are probably the best characterized efflux pumps of Enterobacteriaceae. The effect of AcrAB-TolC on the extrusion of different macrolides has been shown by developing defective (Liu et al, 2009) Ery: erythromycin; Azm: azithromycin; Tel: telithromycin; Jos: josamycin; Clar: clarithomycin; ? : proposed association.…”
Section: Chromosomal Efflux Pumpsmentioning
confidence: 99%
“…Liu et al (2009) reported the presence of functional non-conjugative mef(B) genes, but located in mobilizable plasmids in two different genetic structures in a total of three E. coli isolates. Additionally, another two different genetic structures have also been described in two other isolates carrying a 254 bp fragment of the mef(B) gene truncated by the presence of a IS26.…”
Section: Transferable Efflux Pumpsmentioning
confidence: 99%
“…The plasmidborne Msr(A) transporter, even though mainly responsible for erythromycin efflux in S. aureus [103], is not present in the strain used in our study, S. aureus ATCC 29213 [104]. Mef(A) is closely related to Mef(B), the erythromycin efflux pump in E. coli P475.10.99.C3 [67], and as pyp decreased the final MIC endpoint for induced cultures of this strain (Figures 3(b) and 3(d)), it can be concluded that Mef(A) is an additional candidate for inhibition by pyp in S. aureus.…”
Section: Discussionmentioning
confidence: 78%
“…It is estimated to be quantitatively the second most common in-feed antimicrobial in the U.S. swine production [5] and is also approved for cattle and poultry [59]. [65][66][67]. The strains are best characterized as possessing the following MDR and macrolide efflux pumps: NorA (S. aureus), EmeA (Ent.…”
Section: International Journal Of Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation